Loneliness and Quarter-Life Crisis in Final Year Overseas Students from Outside Java - Melalondo, Militya Christy; Sarajar, Dewita Karema (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
As time goes by there are more demands faced by students, especially when entering their final year. Feelings in the form of fear, anxiety, and worry about the future, including relationships, social life, and career, are also often experienced by individuals, where this phenomenon is called quarter-life crisis. One of the factors that influences a person's quarter-life crisis was their social relationships. For migrant students, loneliness often occurs due to living outside their hometown, far from their parents, and being unable to adapt to the social environment at their place of study. This can encourage someone to experience a quarter-life crisis because the individual feels that he is only fighting alone and there is no presence and support from people around. This study employs a quantitative approach with the objective investigating the correlation between loneliness and quarter-life crisis among final-year students originating from regions outside Java. The subjects in this study were 265 final-year student who have migrated from diverse regions within the country to persue their studies at various universities situated across the Java-island. To measure loneliness and quarter-life crisis, the study utilizes two estabilished instrument, the UCLA Loneliness Scale (Version 3) (α = 0,993) and The Developmental Crisis Questionnaire (α = 0,880). Both instruments are structured with Likert-type scales. The data collected are subjected to analysis using simple regression techniques, facilitated by the statistical software SPSS 25.0-for windows. The findings of this study reveal a statistically significant positive correlation between loneliness and quarter-life crisis, with correlation coefficient r = 0,891 and sig = 0,000 (p < 0,05). The suggest that higher levels of loneliness are associated with a higher likelihood of experiencing quarter-life crisis, whereas lower levels of loneliness are linked to reduced likelihood of encountering quarter-life crisis among final-year student originating from regions outside Java-island. The implications derived from this study underscore the importance for final-year migrant students to enhance the quality of their interpersonal relationship while studying outside their area. This endavor is essential to secure emotional support during challenging periods and to mitigate the risk of being ensnared in a quarter-life crisis.Seiring berjalannya waktu semakin banyak tuntutan yang dihadapi oleh mahasiswa, terutama ketika memasuki tingkat akhir. Perasaan berupa ketakutan, kecemasan, serta kekhawatiran akan masa depan termasuk relasi, kehidupan sosial, dan karier juga seringkali dialami individu, dimana fenomena tersebut disebut dengan quarter-life crisis. Salah satu faktor yang mempengaruhi terjadinya quarter-life crisis pada seseorang adalah relasi sosialnya. Pada mahasiswa perantau, loneliness seringkali terjadi dikarenakan tinggal di luar kampung halaman, jauh dari orang tuanya, dan tidak mampu untuk beradaptasi dalam lingkungan sosial di tempat studinya. Hal ini dapat mendorong seseorang mengalami quarter-life crisis karena individu merasa bahwa dirinya hanya berjuang sendiri dan tidak ada kehadiran serta dukungan dari orang-orang disekitarnya. Penelitian ini merupakan penelitian dengan pendekatan kuantitatif yang bertujuan untuk mengetahui hubungan antara loneliness dengan quarter-life crisis pada mahasiswa perantau tingkat akhir yang berasal dari luar pulau Jawa. Subjek dalam penelitian ini adalah 265 mahasiswa tingkat akhir yang merupakan perantau dari berbagai daerah di Indonesia dan berkuliah di beberapa universitas yang tersebar di pulau Jawa.  Alat ukur yang digunakan dalam penelitian ini adalah UCLA Loneliness Scale (Version 3) (α = 0,993) dan The Developmental Crisis Questionnaire (α = 0,880). Kedua skala tersebut disusun dengan skala model Likert dan diuji menggunakan analisis regresi sederhana dengan uji statistik SPSS 25.0-for windows. Adapun hasil dari penelitian ini ditemukan bahwa terdapat hubungan positif signifikan antara loneliness dan quarter-life crisis, yang ditunjukkan dengan nilai r = 0,891 dan sig = 0,000 (p < 0,05). Artinya semakin tinggi tingkat loneliness, maka semakin tinggi juga tingkat quarter-life crisis, sebaliknya semakin rendah tingkat loneliness, maka semakin rendah juga tingkat quarter-life crisis pada mahasiswa perantau tingkat akhir yang berasal dari luar pulau Jawa. Implikasi dari penelitian ini diharapkan mahasiswa perantau tingkat akhir dapat meningkatkan kualitas relasinya dengan orang lain ketika berada di perantauan agar mampu menemukan dukungan emosional saat berada dalam masa sulit dan tidak terjebak dalam quarter-life crisis.